Literasi Kesehatan Gigi Ibu dan Status Karies Gigi Anak di Wilayah Kumuh Kota Makassar - Liasari, Ira; Priyambodo, R. Ardian; Nur Aida, Wanda (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Mothers' oral health literacy is one of the key factors that can influence children's dental health. In communities with low education levels and health awareness, the risk of dental caries in children tends to be higher. This study aims to examine the relationship between mothers' oral health literacy and children's dental caries status in the slum areas of Makassar. This research is a cross-sectional study involving 101 mother-child pairs in Makassar. Data were collected through an oral health literacy questionnaire filled out by the mothers, and a dental caries index (def-t) examination for the children. Statistical analysis was conducted to assess the relationship between the mothers' oral health literacy and the children's dental caries index, as well as the influence of sociodemographic factors. The study found that the mothers' oral health literacy was divided into three categories: low (34.7%), medium (34.7%), and high (30.7%). The analysis showed no significant relationship between mothers' oral health literacy and children's dental caries status (p=0.113). However, there was a trend indicating a decrease in children's dental caries index as the mothers' oral health literacy increased. In addition, a comparative analysis revealed a significant relationship between the mothers' education level and oral health literacy (p=0.003). The conclusion of this study is that, although the direct relationship between mothers' oral health literacy and children's dental caries status was not statistically significant, improving oral health literacy remains crucial in the effort to prevent dental caries in children. Interventions focusing on enhancing mothers' oral health literacy, particularly among lower-educated communities, are expected to reduce the incidence of dental caries in children